2005
DOI: 10.1162/003355305775097524
|View full text |Cite
|
Sign up to set email alerts
|

Do Lenders Favor Politically Connected Firms? Rent Provision in an Emerging Financial Market

Abstract: Corruption by the politically connected is often blamed for economic ills, particularly in less developed economies. Using a loan-level data set of more than 90,000 firms that represents the universe of corporate lending in Pakistan between 1996 and 2002, we investigate rents to politically connected firms in banking. Classifying a firm as "political" if its director participates in an election, we examine the extent, nature, and economic costs of political rent provision. We find that political firms borrow 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

59
1,343
3
19

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 2,026 publications
(1,424 citation statements)
references
References 15 publications
59
1,343
3
19
Order By: Relevance
“…For the first time, we empirically document that the IPO applications of firms with political capital are more likely to be approved by regulators, which means that political capital also facilitates access to the IPO market. Previous studies have shown that connected firms have easier access to bank loans (e.g., Khwaja and Mian, 2005;Faccio, 2006;Faccio et al, 2006;Claessens et al, 2008). We complement these studies by showing that connected firms are also better able to access funds in the public equity market.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…For the first time, we empirically document that the IPO applications of firms with political capital are more likely to be approved by regulators, which means that political capital also facilitates access to the IPO market. Previous studies have shown that connected firms have easier access to bank loans (e.g., Khwaja and Mian, 2005;Faccio, 2006;Faccio et al, 2006;Claessens et al, 2008). We complement these studies by showing that connected firms are also better able to access funds in the public equity market.…”
Section: Introductionsupporting
confidence: 53%
“…2 See Li et al, 2008. 3 See, for examples, Khwaja and Mian, 2005;Adhikari et al, 2006;Agrawal and Knoeber, 2001;Claessens et al, 2008;Faccio, 2006;Faccio et al, 2006;and Li et al, 2008. 4 See Chaney et al, 2011;and Berkman et al, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Pioneered by Khwaja and Mian (2005), A substantial number of papers have empirically investigated the difference in access to finance between politically connected and politically connected firms. Consistently, in this review, there are 8 papers that specifically address this issue.…”
Section: Access To Financementioning
confidence: 99%
“…7 Remarkably, about 25 per cent of the loans from public banks are granted by banks that explicitly have social objectives. Interestingly, these banks are not used to favor politically connected firms (Khwaja and Mian, 2005). Moreover, after the deregulation of the French banking sector that started in 1985, bank debt declined sharply, especially for poorly performing firms which, as a consequence, were more likely to exit (Bertrand, Schoar, and Thesmar, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These studies also point out the important role the electorate plays in monitoring politicians by showing, for instance, that the rents granted by politicians decrease if electoral participation increases (Sapienza, 2004;Khwaja and Mian, 2005;Cole, 2009). None of the studies, however, compares the costs of granting subsidies through a public bank with other means of subsidization.…”
Section: Introductionmentioning
confidence: 99%